Message from NSPOI Vol.1(1) - Pradhan, Shaili; Humagain, Manoj (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
It is heartwarming to see the Nepalese Society of Periodontology and Oral Implantology progressing from milestone to milestone. With the publication of its own journal in its 3rd annual conference, a new chapter begins. It gives us immense pleasure to share our feelings with you all on the occasion of first publication of Journal of Nepalese Society of Periodontology and Oral Implantology 2017 (JNSPOI). After continuous efforts; finally NSPOI has been successful in having its own journal. The success and continuation of the journal depends on the co-operation and continuous effort of Periodontists and all Dental Fraternity of Nepal. It is our journal so its growth and prosperity is our responsibility. For the journal to thrive and prosper all of us as members of our own dental community have the responsibility to provide articles to let the others know about the kind of service we are imparting inside & outside the country. This is also a medium to share the knowledge and experience among our own colleagues. We are confident that the regular and timely publication of journal will encourage us in undertaking research project and carryout various studies. Finally our heartfelt congratulations and thanks to the editorial board of NSPOI for their tireless effort in the making of JNSPOI. Dr. Shaili Pradhan Founder President NSPOI and Dr. Manoj Humagain Founder General Secretory NSPOI